O ATIVISMO JUDICIAL: RUPTURA À DEMOCRÁTICA REPRESENTATIVIDADE POLÍTICA BRASILEIRA? JUDICIAL ACTIVISM: BREAKS DEMOCRATIC BRAZILIAN POLITICAL REPRESENTATIVITY? (Revista Direito em Debate, 2021)
Judicial activism is considered of high relevance and complexity in the contemporaneity of Brazilian law. From such conjectures and discussions, many emblematic activist cases have been extracted by the Judiciary. On the other hand, the constant observation of judicial activism is directly related to a crisis of political representativeness that is affected by an inertia and / or omission of the political powers, that is, Legislative and Executive Powers. Thus, using a theoretical-juridical methodology with deductive reasoning, through doctrinal and jurisprudential analysis will be observed important factors that directly influence the enhancement of the Judiciary through judicial activism conferring a rupture the political representation democratically guaranteed by the Brazilian Federal Constitution.